Blockchain-Assisted Resilient Control for Distributed Energy Resource Management Systems - Seerin Ahmad; Kalyan Nakka; Taesic Kim; Dongjun Han; Dongjun Won; Bohyun Ahn (IEEE Access)
Grid resilience has become a paramount concern in today’s dynamic energy landscape, wherein the mass integration of distributed energy resources (DERs) plays a crucial role in achieving flexible and resilient power grids. A DER management system (DERMS) is a remote monitoring and control system managing DERs in a distribution system, which is becoming increasingly important for a DER-rich power grid. However, an outstanding issue is a single point of failure of the centralized DERMS by cyberattacks, which threatens grid stability and results in regional power outages in the worst case. This paper proposes a novel approach to address the resilience challenges faced in the centralized DERMS through the development of a blockchain (BC)-assisted resilient control mechanism. The main idea is to create a virtual DERMS monitoring and control using BC smart contract and network that takes over seamlessly in the event of a failure of the DERMS. This BC system enables securely sharing DER and grid data among BC clients and provides control commands to DERs when the DERMS is a denial-of-service condition. To demonstrate the effectiveness of the proposed BC-assisted DERMS, voltage and frequency control recovery cases are tested in a real-time hardware-in-the-loop DER system testbed.